cos(5pi/6) = cos(pi - pi/6)
cos(pi - pi/6) = cos(a + b) = cos(a)cos(b) - sin(a)sin(b)
cos(pi - pi/6) = cos(pi)cos(pi/6) - sin(pi)sin(pi/6)
cos(pi - pi/6) = -(root3)/2 - 0
cos(pi - pi/6) = -(root3)/2
cos(5pi/6) = -(root3)/2
there u go, just remember the cos(a + b) formula.
2007-07-10 10:17:57
·
answer #1
·
answered by Anonymous
·
1⤊
1⤋
cos (5pi/6) = cos(2pi/6 + 3pi/6) = cos(pi/3 + pi/2)
Now use the sum formula:
cos(pi/3 + pi/2) = cos(pi/3)cos(pi/2) - sin(pi/3)sin(pi/2)
= (1/2)(0) - (sqrt(3)/2)(1)
= - sqrt(3)/2
This is a pretty silly way to figure this out. You can also just know that 5pi/6 has a reference angle of pi/6, and it's in the second quadrant, where cosine is negative. So cos(5pi/6) = -cos(pi/6) = -sqrt(3)/2.
2007-07-10 10:22:03
·
answer #2
·
answered by pki15 4
·
0⤊
0⤋
i do no longer kow the way you're breaking seventy 5 up. Trig SUM: cos (A + B)= cosA*cosB - sinA*sinB difference: cos (A - B) = cosA*cosB + sinA*sinB ex) sin 30 = a million/2, cos 30= ?3/2, sin 40 5 = cos 40 5= ?2/2 cos seventy 5 = cos(40 5 + 30) = cos 40 5 * cos 30 - sin 40 5 * sin 30 =?2/2 * ?3/2 - ?2/2 * a million/2 ? ?6/4 -?2/4 very final answer: (?6 - ?2)/4
2016-11-08 22:51:40
·
answer #3
·
answered by gracely 4
·
0⤊
0⤋
cos (5pi/6) = cos 150 degrees = -.8660254036
Also, cos (5pi/6) = -sqrt(3)/2 for an exact answer.
2007-07-10 10:20:56
·
answer #4
·
answered by ironduke8159 7
·
0⤊
0⤋
cos (5pi/6)=
cos(pi-(pi/6)=
-cos(pi/6)=
-√3/2
2007-07-10 10:22:46
·
answer #5
·
answered by cvet_che 2
·
0⤊
0⤋
cos (5π / 6) = - cos (π / 6) = - √3 / 2
2007-07-10 10:43:38
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
And, after all that, do you know where the root3 over two comes from ?
2007-07-10 12:35:52
·
answer #7
·
answered by Twiggy 7
·
0⤊
0⤋
It's equal to - 0.5*sqrt(3). What do you want to do with it?
2007-07-10 10:18:42
·
answer #8
·
answered by cattbarf 7
·
0⤊
0⤋